Shoes industry is an important sector which contributes significantly to the national and local government’s revenue and advantages to the local community to reduce unemployment and poverty. The objective of this research is to analyze local economic development of sustainable shoes industry, especially the environmental impact at Bogor. This research uses appraisal for local economic development for shoes industry analysis (ALEDIA), modification from Rapid Assessment for Local Economic Develo - Riny Kusumawati; Hermanto Siregar; Sugeng Budiharsono; Wonny A. Ridwan (Forum Pasca Sarjana, 2010)
Shoes industry is an important sector which contributes significantly to the national and local government’s revenue and advantages to the local community to reduce unemployment and poverty.  The objective of this research is to analyze local economic development of sustainable shoes industry, especially the environmental impact at Bogor.  This research uses appraisal for local economic development for shoes industry analysis (ALEDIA), modification from Rapid Assessment for Local Economic Development (RALED).  The result shows that the sustainability index of shoes industry at Bogor is bad/unsustainable (34.84).  Its sustainability includes economy, ecology, social, institution, technology and policy aspects.  Based on the strategic policy implementation, the sustainability index of shoes industry at Bogor is good/sustainable (55.82).   Key words: local economic development, sustainable development